Night eating syndrome – prevalence characteristics of the health problem - Olejniczak, Dominik; Skonieczna, Joanna; Kitowska, Wioleta (Journal of Education, Health and Sport, 2018)
Night eating syndrome (NES) is a relatively recent problem and despite the increase in the number of publications over the last years, it is still often underdiagnosed and its methods of treatment are still being developed. Over the past years, various definitions of NES have appeared, and the lack of a comprehensive version significantly impeded the comparison of research results and delayed in-depth knowledge of the syndrome. People who have been diagnosed with NES should be monitored for stress and anxiety disorders. Consideration should be given to the use of appropriate treatment methods, such as relaxation training or exercises in coping skills. Night eating syndrome can be inductive to becoming overweight and obese. Further research into this health problem is recommended. Inclusion of night eating syndrome during diagnosis in patients with type 2 diabetes, insomnia, and other eating disorders or mental health problems should be taken into account.